Science and sociality: achieving the social dimensions of science through contextualization of secondary school classroom instruction - Dr. Uchenna Kingsley Okeke; Professor Sam Rmaila (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2024)
This position paper is predicated on two focus areas. First, it recognises that scientific inquiry is performed in social situations and questions whether and how standard epistemology can be augmented to tackle this aspect. Within this focus, the goals of science education are reviewed. The second focus addresses sociality as an essential feature of knowledge and questions how standard epistemology can be reformed from this generally social perspective. Specifically, this study on one hand addresses the social dimension of science education, and on the other hand, examines the suitability of instructional contextualisation as a possible strategy to achieve the social dimensions of science education. The aim is to initiate a conversation about the importance of framing science education studies and experiences within the sociocultural context of interests and needs to achieve reliable participation of all concerned. To this end, this paper argues that science education ought to place considerable emphasis on students' acquisition of values and skills of sociality. Furthermore, a comprehensive goal of science education should constitute both the normative and the non-normative aspects of science with a particular emphasis on the development of character formation, moral values, creativity skills and competences. There is, therefore, a need for an examination of the social dimensions of science education and its curriculum implications, especially as science education serves as the nexus between science and society.